2020
DOI: 10.1177/1558944719895780
|View full text |Cite
|
Sign up to set email alerts
|

Hand It to Dr Google: The Quality of Online Information on Ganglion Cysts

Abstract: Background: The internet is becoming a common source of health information for hand surgery patients. This study evaluates the quality of web-based resources on ganglion cysts of the hand. Methods: We completed a search for “ganglion cyst” on 3 search engines (Google, Dogpile, and Yippy). The quality of the top-100 patient education websites was assessed using a validated internet rating tool. Websites were evaluated based on affiliation, accountability, currency, interactivity, website organization, readabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…[26][27][28][29][30][31][32][33]45 The use of health-specific CTR is a unique aspect of this readability analysis, and it enabled specific study of the search results most likely encountered by patients. The majority of prior readability analyses have considered larger sample sizes of URL results, sometimes including as many as 100 query results for analysis 13,[26][27][28][29][30][31][32][33] ; this process is unnecessary when taking health-specific CTR data into account. In addition, a readability analysis of nonmelanoma skin cancers by Basch et al 26 showed that the composite readability scores do not differ significantly between SERP pages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30][31][32][33]45 The use of health-specific CTR is a unique aspect of this readability analysis, and it enabled specific study of the search results most likely encountered by patients. The majority of prior readability analyses have considered larger sample sizes of URL results, sometimes including as many as 100 query results for analysis 13,[26][27][28][29][30][31][32][33] ; this process is unnecessary when taking health-specific CTR data into account. In addition, a readability analysis of nonmelanoma skin cancers by Basch et al 26 showed that the composite readability scores do not differ significantly between SERP pages.…”
Section: Discussionmentioning
confidence: 99%
“…The authors' evaluation of the literature also indicated that the most validated and high-yield tools for readability are the five indices used in this study. [26][27][28][29][30][31][32][33]45 The use of health-specific CTR is a unique aspect of this readability analysis, and it enabled specific study of the search results most likely encountered by patients. The majority of prior readability analyses have considered larger sample sizes of URL results, sometimes including as many as 100 query results for analysis 13,[26][27][28][29][30][31][32][33] ; this process is unnecessary when taking health-specific CTR data into account.…”
Section: Discussionmentioning
confidence: 99%
“…These reviewers were gynecologists with further training and expertise in menopause and mature women's health. Five reviewers were included to further improve the reliability and accuracy of subjective scores, as studies evaluating website content typically only use two to three reviewers 26-30 . All reviewers were trained using tool-specific instructions to score each item.…”
Section: Methodsmentioning
confidence: 99%
“…Five reviewers were included to further improve the reliability and accuracy of subjective scores, as studies evaluating website content typically only use two to three reviewers. [26][27][28][29][30] All reviewers were trained using tool-specific instructions to score each item. For the DISCERN Instrument, reviewers were provided additional instructions from its handbook (http://www.discern.org.uk/discern.pdf).…”
Section: Website Content Analysismentioning
confidence: 99%
See 1 more Smart Citation